Economic growth and biodiversity: An overview. Conservation policies in Africa - Bi Goli Jean Jacques Iritié (Journal of Sustainable Development, 2015)
From the economic literature on the relationship between economic growth and environment pioneered by Grossman and Krueger (1991) and Shafik and Bandyopadhyay (1992) we first conduct a theoretical and critical reflection on the existence of a Kuznets curve for biodiversity. It appears that results are strongly contrasted; economic growth does not seem to be necessarily the solution of biodiversity loss. Then, we focus on the main biodiversity conservation policies implemented in Africa (with the example of Côte d'Ivoire), i.e. protected areas and we discuss its effectiveness in achieving the dual objective of conservation and economic development for local communities.
Keywords: Q01; Q50; Q57; 330; Economic growth; Environmental Kuznets curve; Biodiversity conservation policies; Protected areas; Africa; Côte d'Ivoire